2011
DOI: 10.4319/lo.2011.56.5.1824
|View full text |Cite
|
Sign up to set email alerts
|

Carbon self‐utilization may assist Caulerpa taxifolia invasion

Abstract: Additions of 13 C-labeled macroalgal detritus (Caulerpa taxifolia) and seagrass detritus (Zostera capricorni) to a vegetated intertidal mudflat in subtropical Australia provided insight into the mechanisms and ecosystem effects of C. taxifolia invasions in seagrass beds. Despite the high lability typical of macroalgae, carbon from seagrass detritus was removed from sediments and transferred to benthic compartments (microphytobenthos, bacteria, mud whelks, and live C. taxifolia and Z. capricorni) at a faster ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
95
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(96 citation statements)
references
References 41 publications
1
95
0
Order By: Relevance
“…Cook et al (2007) recovered only 1-5% of fixed carbon as DOC. In contrast, Oakes et al (2010b) reported loss from in situ surficial subtropical photic sands of 85% of MPB-derived carbon over 33 d. The pathways responsible for this loss were not determined, but this highlights that loss to the water column may be the main fate of carbon fixed by MPB in this environment. Alternatively, carbon may have been buried deeper within sediments (below 2 cm; Oakes et al 2010b).…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Cook et al (2007) recovered only 1-5% of fixed carbon as DOC. In contrast, Oakes et al (2010b) reported loss from in situ surficial subtropical photic sands of 85% of MPB-derived carbon over 33 d. The pathways responsible for this loss were not determined, but this highlights that loss to the water column may be the main fate of carbon fixed by MPB in this environment. Alternatively, carbon may have been buried deeper within sediments (below 2 cm; Oakes et al 2010b).…”
mentioning
confidence: 87%
“…MPB can affect movement of nutrients, oxygen, and carbon across the sediment-water interface (Cahoon 1999;Eyre and Ferguson 2005). Particularly where nutrients are limited (Cook et al 2007), much of the carbon fixed by MPB is secreted as extracellular polysaccharides (EPS; up to 73% of productivity; Goto et al 2001), primarily carbohydrates (Underwood et al 2004;Oakes et al 2010b). EPS reduces resuspension by stabilizing sediments (Cahoon 1999) and, in addition to direct grazing on MPB, can be a significant labile carbon source for consumers .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The concentrations and δ 13 C of DOC and DIC were measured via continuous-flow wet-oxidation isotope-ratio mass spectrometry using an Aurora 1030W total organic carbon analyzer coupled with a Thermo Delta V Plus Isotope Ratio Mass Spectrometer (IRMS) as described by Oakes et al (2011).…”
Section: Sample Analysismentioning
confidence: 99%
“…Middelburg et al, 2000;Oakes et al, 2010b;Evrard et al, 2012). More recently carbon stable isotope labeling has also been used to trace pathways of loss for MPB-derived carbon, including fluxes of DIC (Evrard et al, 2010, Oakes et al, 2011Oakes et al, 2012) and DOC (Oakes et al, 2011;Oakes et al, 2012), and loss of CO 2 due to respiration of algal carbon (phytodetritus) in intertidal sediments (Maher et al, 2013;. Carbon stable isotope labeling has been used in a few studies in intertidal muds and sands and shallow subtidal sands in temperate regions to investigate the processing of MPB-derived carbon, but there has been only one study in the subtropics, which looked at shallow subtidal sands (Oakes et al, 2012).…”
Section: Introductionmentioning
confidence: 99%